2021
DOI: 10.1093/bjs/znab068
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic sublay non-absorbable mesh positioning following midline laparotomy in a clean-contaminated field: randomized clinical trial (PROMETHEUS)

Abstract: Background Incisional hernia is a frequent postoperative complication after midline laparotomy. Prophylactic mesh augmentation in abdominal wall closure after elective surgery is recommended, but its role in emergency surgery is less well defined. Methods This prospective randomized trial evaluated the incidence of incisional hernia in patients undergoing urgent midline laparotomy for clean-contaminated surgery. Closure using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…Still, since there is a growing interest in using alternative materials for mesh, it could be interesting to make a further evaluation on the impact of costs on outcomes of their implementation into clinical practice. [20,21] Finally, as reported by Bracale et al, one of the major limitations in comparing laparoendoscopic and open surgical techniques is that scientific papers often compare bilateral vs monolateral hernias. [9] From the data analysis, we can observe that there has been a progressive increase in the laparoendoscopic approach to inguinal hernia repair in Italy, together with an increase in the number of emergency operations performed for incarcerated hernias, showing a boost in confidence in the minimally invasive approach to inguinal hernioplasty even in more complex situations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Still, since there is a growing interest in using alternative materials for mesh, it could be interesting to make a further evaluation on the impact of costs on outcomes of their implementation into clinical practice. [20,21] Finally, as reported by Bracale et al, one of the major limitations in comparing laparoendoscopic and open surgical techniques is that scientific papers often compare bilateral vs monolateral hernias. [9] From the data analysis, we can observe that there has been a progressive increase in the laparoendoscopic approach to inguinal hernia repair in Italy, together with an increase in the number of emergency operations performed for incarcerated hernias, showing a boost in confidence in the minimally invasive approach to inguinal hernioplasty even in more complex situations.…”
Section: Discussionmentioning
confidence: 98%
“…Still, since there is a growing interest in using alternative materials for mesh, it could be interesting to make a further evaluation on the impact of costs on outcomes of their implementation into clinical practice. [ 20 , 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade there has been intensive studies and trials on the prevention and reduction of incisional hernias and the main focus was on the technique as it is the only independent factor that is controlled by the surgeon. Many techniques have been explored, including use of prophylactic mesh [ 9 ], distance of stitches from sheath edge and each other (5 mm instead of the conventional 10 mm in mass closure), and different types of suture materials and length [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have discussed the benefits of prophylactic mesh closure in midline laparotomy 30,31 . Pizza et al 32 . demonstrated that prophylactic mesh in clean contaminated wounds was safe and reduced the incidence of incisional hernia following laparotomy.…”
Section: Discussionmentioning
confidence: 99%